Students' emotions of enjoyment and boredom and their use of cognitive learning strategies – How do they affect one another?. (April 2020) - Obergriesser, Stefanie; Stoeger, Heidrun
Abstract: To better understand the relationship between enjoyment and boredom and students' use of cognitive learning strategies, we analyzed both directions of effects between these constructs as described in the control-value theory of achievement emotions (Pekrun, 2006; 2018). Our study used a sequential design in which students' (N = 338 4th grade students) effective use of cognitive learning strategies was measured in real learning situations, allowing insights into the temporal order of effects and discrimination between intra- and interindividual effects (N = 8020 assessments within students). An increased intraindividual level of enjoyment positively predicted subsequent effective use of learning strategies, whereas effective use of learning strategies did not predict students' subsequent enjoyment on the intraindividual level. Interindividual differences in enjoyment and effective use of cognitive learning strategies were unrelated, whereas negative relations were found for boredom and effective strategy use. On the intraindividual level, boredom and effective strategy use were unrelated. Highlights: Enjoyment and boredom are related to the effective use of learning strategies. Using a sequential design, both directions of effects were examined. Enjoyment, but not boredom positively predicted the effective use of learning strategies. The effective use of learning strategies did not predict enjoyment and boredom.